Computing satellite networks—the novel development of computing-empowered space-air-ground integrated networks - Pingke DENG; Tongxu ZHANG; Nanxiang SHI; Tong ZHANG; Tianzhu SHAO; Shaowen ZHENG (Dianxin kexue)
Facing the increasing demands for computing ability and network access, the space-air-ground integrated networks in 6G systems is expected to surmount the limits on a single point of computing ability and traditional network transmission through the advantages of network cluster, where the novel space-air-ground integrated networks that deeply integrate cloud, edge, terminal, network, data, and computation is subsequently formed by taking computing ability as the core and network infrastructure as the foundation.Initially, the current situation and development in existing computing force networks and space-air-ground integrated networks (SAGIN) was introduced.Along with the demands for 6G computing-empowered space-air-ground integrated networks, the concept of satellite computing networks was defined and the co-existed system of computing capability and communication networks was further discussed.Then, the space networks, air networks, and ground networks of the layered satellite computing network architecture were discussed.Based on that, its logical network architecture that includes computing resource layer, computing abstract layer, and computing orchestration layer was further introduced.After that, the key technology enablers with respct to computing and storage issue, trusted transmission issue, satellite computing force addressing issue, and high-mobility computing force routing issue was discussed.Finally, the typical applicaiton scenarios of satellite computing networks and envision its future was presented.